2015
DOI: 10.1177/0148607115583675
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Related to Protein Delivery in a Critically Ill Population

Abstract: Achieving at least 80% of prescribed protein intake may be important to survival and shorter TDA in ICU patients. Efforts to achieve prescribed protein intake should be maximized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
209
2
21

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(251 citation statements)
references
References 37 publications
10
209
2
21
Order By: Relevance
“…Uma menor oferta calórica em pacientes internados em UTI está associada ao aumento nos episódios de hipoglicemia (28)(29)(30) , infecções severas (31) , maior tempo de internação (32) , maiores gastos com a saúde desses indivíduos (33) e aumento nas taxas de mortalidade (31,34) . O consenso canadense para terapia nutricional em paciente crítico preconiza que o acompanhamento diário e o rígido controle do protocolo de nutrição enteral da UTI por parte da EMTN deve facilitar um maior recebimento da dieta prescrita (35) .…”
Section: Discussionunclassified
“…Uma menor oferta calórica em pacientes internados em UTI está associada ao aumento nos episódios de hipoglicemia (28)(29)(30) , infecções severas (31) , maior tempo de internação (32) , maiores gastos com a saúde desses indivíduos (33) e aumento nas taxas de mortalidade (31,34) . O consenso canadense para terapia nutricional em paciente crítico preconiza que o acompanhamento diário e o rígido controle do protocolo de nutrição enteral da UTI por parte da EMTN deve facilitar um maior recebimento da dieta prescrita (35) .…”
Section: Discussionunclassified
“…Even with this low level of protein target, our patient only received approximately 62.4% of this target, with the average of approximately 0.75g/kg body weight. This level is dangerously low given the facts that there were a strong association of protein intake and clinical outcomes among critically ill patients 3,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that 88.2% of our high nutrition risk patients were underfed, it is plausible that both feeding inadequacy and disease severity are affecting patients' survival. Many large multi-centre research had been done and confirmed the relationship between feeding adequacy and clinical outcomes after adjusting for disease severity status 2,3,19 , especially in patients with high nutrition risk 6 A Malaysian cohort study on nutritional support practices in ICU is eagerly awaited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 It may be more important to ensure protein adequacy as studies have shown that improvement of clinical outcomes is associated with adequate protein intake, even after adjustment for energy adequacy. 9,10 . However, caution also need to be taken to avoid overfeeding patients, which is usually defined as feeding over 110% of energy prescribed, 11 as it is associated with complications such as hyperglycemia, azotemia, hypertriglyceridemia, electrolyte imbalance, immunosuppression, alteration in hydration status, hepatic steatosis, and difficulty waning from mechanical ventilation.…”
Section: Feeding Adequacy Among Critically Ill Patients In the Intensmentioning
confidence: 99%